(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
In this article, we delve into the fundamental concepts of topological complexity and explore the algorithms that enable us to analyze and interpret data shapes effectively. From the foundational principles of topology and simplicial complexes to advanced computational techniques like persistent homology and Mapper, we uncover how TDA offers a unique perspective on data analysis.